Proceedings of the 2017 Internet Measurement Conference 2017
DOI: 10.1145/3131365.3131379
|View full text |Cite
|
Sign up to set email alerts
|

Inferring BGP blackholing activity in the internet

Abstract: The Border Gateway Protocol (BGP) has been used for decades as the de facto protocol to exchange reachability information among networks in the Internet. However, little is known about how this protocol is used to restrict reachability to selected destinations, e.g., that are under attack. While such a feature, BGP blackholing, has been available for some time, we lack a systematic study of its Internet-wide adoption, practices, and network ecacy, as well as the prole of blackholed destinations. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 44 publications
8
68
0
Order By: Relevance
“…We obtain a data set of inferred blackholing events from publicly available BGP routing data, using a measurement system that we implemented on the basis of the methodology described by Giotsas et al [11].…”
Section: Blackholing Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…We obtain a data set of inferred blackholing events from publicly available BGP routing data, using a measurement system that we implemented on the basis of the methodology described by Giotsas et al [11].…”
Section: Blackholing Eventsmentioning
confidence: 99%
“…3 Blackholing Communities -Within the BGP data, we look for BGP announcements tagged with a community that is likely to signal a blackholing request. Giotsas et al [11] created a dictionary of such communities by applying natural language processing to resources where blackholing communities are likely to be documented (e.g., in Internet Routing Registry (IRR) records). We use a copy of this dictionary, which provides us with 288 asn:value community tags, for 251 blackholing providers, using 74 distinct values (e.g., 666).…”
Section: Blackholing Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Giotsas et al examined communities that geographically tag route origins and found that there were no standardized values across providers [57]. In addition, even though RFC 7999 standardizes the black hole community [64], Giotsas et al found that several nonstandard variants still exist and some ASes do not adhere to the proper implementation of the standard (particularly regarding the propagation of blackholed prefixes) [58]. The severe lack of standardization and centralized documentation for BGP communities has caused researchers to resort to applying natural language processing on routing policies as a means of measuring large scale community usage [57,58].…”
Section: Related Workmentioning
confidence: 99%
“…In addition, even though RFC 7999 standardizes the black hole community [64], Giotsas et al found that several nonstandard variants still exist and some ASes do not adhere to the proper implementation of the standard (particularly regarding the propagation of blackholed prefixes) [58]. The severe lack of standardization and centralized documentation for BGP communities has caused researchers to resort to applying natural language processing on routing policies as a means of measuring large scale community usage [57,58]. We considered this approach but instead opted to manually parse routing policies from a smaller number of ASes to eliminate potential inaccuracies and extract more nuanced levels of community support.…”
Section: Related Workmentioning
confidence: 99%